Improving the Nature and Classification of Overhead Costs (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses the theoretical aspects of overhead costs, their importance for the formation of the cost of production and the problems of accounting. The classification of overhead costs according to various characteristics, including economic elements, functional role and variability of costs is given. Modern methods of accounting and distribution of overhead costs, such as the method of coefficients, step-by-step distribution and ABC-costing, are analyzed overhead costs associated with their variability and complexity of distribution, as well as the need to introduce modern information systems to improve the accuracy of accounting. In conclusion, recommendations are given for improving the methods of accounting and management of overhead costs at enterprises.